Rule-formulation and binding precedent in the madhhab-law tradition : Ibn Qutlubugha's commentary on the compendium of Quduri - Al-Azem, Talal (Leiden ; Boston : Brill, 2017)
In Rule-Formulation and Binding Precedent in the Madhhab-Law Tradition , Talal Al-Azem argues for the existence of a madhhab -law tradition' of jurisprudence underpinning the four post-classical Sunni schools of law. This tradition celebrated polyvalence by preserving the multiplicity of conflicting opinions within each school, while simultaneously providing a process of rule formulation ( tarjīḥ ) by which one opinion is chosen as the binding precedent ( taqlīd ). The predominant forum of both activities, he shows, was the legal commentary. Through a careful reading of Ibn Quṭlūbughā's (d. 879/1474) al-Taṣḥīḥ wa-al-tarjīḥ , Al-Azem presents a new periodisation of the Ḥanafī madhhab , analyses the theory of rule formulation, and demonstrates how this madhhab -law tradition facilitated both continuity and legal change while serving as the basis of a pluralistic Mamluk judicial system.
‎3.3. Arguments of Language and Logic‎3.4. Arguments from Revelation and the Early Muslim Community; ‎3.5. Arguments from Scholarship; ‎3.6. Justifications from Juristic Considerations; ‎3.7. Justifications from Context; ‎3.8. Justifications from Exigencies of Change and Necessity; ‎3.9. Justifications of Lifting Difficulty and Facilitating Ease; ‎3.10. Justifications of Preceding Juristic Authority; ‎4. Operative Principles of Rule-Determination; ‎5. The Degree of Congruence between Theory and Practice; ‎Conclusion; ‎Appendix 1. The Writings of Qudūrī
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Ibn Quṭlūbughā, al-Qāsim ibn ʻAbd Allāh, -- 1399 or 1400-1474 or 1475.; Qudūrī, Aḥmad ibn Muḥammad, -- 972 or 973-1037.; Ibn Quṭlūbughā, al-Qāsim ibn ʻAbd Allāh, -- 1399 or 1400-1474 or 1475.; Mukhtaṣar al-Qudūrī (Qudūrī, Aḥmad ibn Muḥammad); Islamic law -- Interpretation and construction; Hanafites; LAW -- Essays; LAW -- General Practice; LAW -- Jurisprudence; LAW -- Paralegals & Paralegalism; LAW -- Practical Guides; LAW -- Reference; Hanafites; Islamic law -- Interpretation and construction; Electronic books